Price points and price rigidity - Daniel Levy; Dongwon Lee; Haipeng (Allan) Chen; Robert J. Kauffman; Mark Bergen (Bar-Ilan University, Department of Economics, 2010)
We study the link between price points and price rigidity, using two datasets: weekly scanner data, and Internet data. We find that: 9 is the most frequent ending for the penny, dime, dollar and ten-dollar digits; the most common price changes are those that keep the price endings at 9; 9-ending prices are less likely to change than non-9-ending prices; and the average size of price change is larger for 9-ending than non-9-ending prices. We conclude that 9-ending contributes to price rigidity from penny to dollar digits, and across a wide range of product categories, retail formats and retailers.
Keywords: 330; Preisrigidität; Anpassungskosten; Preismanagement; Chicago (Ill.)